Rephaim, Whisperers, and the Dead in Isaiah 26: 13-19: A Ugaritic Parallel - McAffee, Matthew (Journal of Biblical literature, 2016)
The main aim of this study is to reexamine the meaning of Isa 26:13-19 with particular attention to the identity of the Rephaim in v. 14, the sense of lḥ in v. 16, and the twofold understanding of the metîm ("the dead") in vv. 14 and 19. In doing so, one must also consider the importance of the Ugaritic Rapa¸ūma and their role in the textual materials of Ugarit as a possible background for Isa 26. I argue that the text of Isaiah pronounces judgment on those who clamor after the trappings of the Rephaim by denying their purported powers. The text, then, attempts to condemn a more popularized variety of Yahwism, one that is open to the powers of the dead and the resort to magical charms. This appeal culminates in the expressed hope of resurrection in v. 19.